Assessment of Effect of Glass Fiber on the Geotechnical Properties of Black Cotton Soil. Issue 1 (1st January 2023) - Singh, Dharmendra; Kumar, Vijay; Tiwari, R.P.
Abstract: Black cotton soil (BCS) has now been declared as one of the poorest soil among all soils regarding civil engineering construction projects due to presence of its inherent clay mineral i.e. montmorillonite, which introduces undesirable shrinkage and swelling in the BCS. BCS should not be used directly in civil engineering projects because of its excessive volume change behavior. The sample of black cotton soil for the study has been collected from district Narsinghpur near the Bikrampur railway station, Madhya Pradesh, India. Evaluation of effect of glass fiber addition on the strength properties of BCS is described in this research article. Glass fiber acquires good properties such as stiffness, high strength, resistance and flexibility to chemical loss. Glass fiber has been mixed with oven dried BCS from 2% to 8% by its weight. Geotechnical properties are thoroughly investigated before and after treating the BCS sample by means of various laboratory tests. For both treated and untreated BCS samples, UCS testing was performed with varying curing time of 0, 4, 7, 14, 28 and 56 days. UCS value was found to be decreased due to water holding capacity of glass fiber. The laboratory findings indicate that for all additives, MDD and expansion ratio of the BCS decreases, whereas OMC and CBR value increases. XRD (X-ray diffraction) analysis has been conducted on untreated and glass fiber treated BCS samples to estimate change in microstructure and mineralogical composition.